Investigation of the Expression of Inflammatory Markers in Oral Biofilm Samples in Patients with Systemic Scleroderma and the Association with Clinical Periodontal Parameters—A Preliminary Study - Mayte Buchbender; Amelie Lugenbühl; Jakob Fehlhofer; Christian Kirschneck; Jutta Ries; Rainer Lutz; Michael Sticherling; Marco Rainer Kesting (Life, 2021)
Background: Systemic scleroderma (SSc) has multiple orofacial effects. The aim of this study was to analyze the expression of inflammatory mediators in biofilm samples. It was hypothesized that different expression levels and clinical associations might be drawn. Methods: A total of 39 biofilm samples from group 1 = SSc and group 2 = healthy control were examined for the expression levels of interleukin (IL)-2,-6, and -10; matrix metalloprotease (MMP)-9; and surface antigens CD90 and CD34 by quantitative real-time PCR and clinical parameters. Relative quantitative (RQ) gene expression was determined using the ∆∆CT method. Results: The mean bleeding on probing values (p = 0.006), clinical attachment loss (CAL) (p = 0.009), gingival recession (p = 0.020), limited mouth opening (p = 0.001) and cervical tooth defects (p = 0.011) were significantly higher in group 1. RQ expressions of IL-2 and CD34 were significantly lower, IL-6, MMP-9, and CD90 were significantly higher. There was a significant positive correlation of IL-6/MMP-9 and negative correlation of mouth opening/CAL and IL-6/CAL. Conclusion: Different expression levels of IL-2, IL-6, MMP-9, CD34 and CD90 were detected in biofilm samples from patients with SSc compared to control. An immunological correlation to the clinical parameters of mouth opening and CAL was shown; thus, we conclude that SSc might have an impact on periodontal tissues.